2010
DOI: 10.3347/kjp.2010.48.3.195
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis ofToxoplasma gondiiKI-1 Tachyzoites

Abstract: Abstract:We studied on the proteomic characteristics of Toxoplasma gondii KI-1 tachyzoites which were originally isolated from a Korean patient, and compared with those of the well-known virulent RH strain using 2-dimensional electrophoresis (2-DE), mass spectrometry, and quantitative real-time PCR. Two-dimensional separation of the total proteins isolated from KI-1 tachyzoites revealed up to 150 spots, of which 121 were consistent with those of RH tachyzoites. Of the remaining 29 spots, 14 showed greater than… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…Rapid developments in proteomic techniques have provided novel approaches for proteomic studies of human and animal pathogens for elucidating the cellular responses toward infection, which will facilitate the identification of potential anti-infection drug targets and development of new diagnostic methods (Ye et al 2010). Several proteomic studies have been performed on T. gondii, which have helped to elucidate the specialized invasion organelles and their composition, as well as proteins associated with the cytoskeleton (Bradley et al 2005;El Hajj et al 2006;Kawase et al 2007;Fauquenoy et al 2008;Xia et al 2008;Ma et al 2009;Weiss et al 2009;Choi et al 2010;Che et al 2011). Nelson et al (2008 reported proteomic analysis of Toxoplasma-infected human foreskin fibroblasts (HFFs) in vitro, which indicated that the proteome of host cell responded in a dramatic way to T. gondii invasion.…”
Section: Introductionmentioning
confidence: 98%
“…Rapid developments in proteomic techniques have provided novel approaches for proteomic studies of human and animal pathogens for elucidating the cellular responses toward infection, which will facilitate the identification of potential anti-infection drug targets and development of new diagnostic methods (Ye et al 2010). Several proteomic studies have been performed on T. gondii, which have helped to elucidate the specialized invasion organelles and their composition, as well as proteins associated with the cytoskeleton (Bradley et al 2005;El Hajj et al 2006;Kawase et al 2007;Fauquenoy et al 2008;Xia et al 2008;Ma et al 2009;Weiss et al 2009;Choi et al 2010;Che et al 2011). Nelson et al (2008 reported proteomic analysis of Toxoplasma-infected human foreskin fibroblasts (HFFs) in vitro, which indicated that the proteome of host cell responded in a dramatic way to T. gondii invasion.…”
Section: Introductionmentioning
confidence: 98%
“…More than 163 and 150 protein spots from T . gondii strains RH and KI-1 tachyzoites, in corresponding order, were detected by 2-DE within a pH range of 3–10 after silver staining [ 32 ]. A high-resolution 2-DE gel separation over pH ranges 4–7 and 6–11 was also exploited to distinguish over 1000 polypeptides spots [ 20 ], and in a separate study, 1,227 protein spots of T .…”
Section: Discussionmentioning
confidence: 99%
“…[131415] Thus, in principle, ESA could play a role in the persistent stimulation of cell–mediated immunity in chronically infected healthy subjects. Excretory/secretory antigens may be the best form of antigens for stimulation of the cell-mediated immune response and a good candidate as a vaccine for toxoplasmosis prevention.…”
Section: Discussionmentioning
confidence: 99%